The dynamic relationship between money supply and economic growth - Antoni Antoni (Universitas Islam Indonesia, 2015)
This study analyzes the influence of the financial sector to economic growth in Indonesia. The variables used are the country's financial sectors which are narrow money (M1), broad money (M2) and money the broadest money (M3), with an interest rate as a control variable. Economic growth is represented by Gross Domestic Product and producer price index. The analysis is performed using an Autoregressive Distributed Lag model (ARDL). The stability test is conducted using CUSUM test to see the changes in the structure and the effect of disruption to financial sector development relationship of economic growth. ARDL analysis results indicate that the development of the financial sector has a significant relationship with the country's economic growth. CUSUM analysis results suggest that the relationship of financial sector development-economic growth is stable against changes in economic structure.